Pendekatan Kontekstual Terhadap Tradisi Peringatan Kematian Dalam Pelayanan Pastoral Di Gereja Gladagsari, Boyolali. - Nugroho, Yulianto; Pramono, Teguh (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2026)
The death commemoration ritual is an integral component of the symbolic system within Javanese society, reflecting a collective understanding of death as both a spiritual and social transition. In Gladagsari Village, Boyolali, this practice is not merely a religious rite but also a sociocultural mechanism that reinforces communal solidarity and cohesion. For Christians embedded within such a cultural framework, a hermeneutical tension arises between doctrinal fidelity to the authority of Scripture and the pastoral necessity of harmonious coexistence with local traditions. This study employs a qualitative case study approach, utilizing in-depth interviews, participant observation, and literature review, analyzed through an interpretive framework grounded in contextual pastoral theology. The findings reveal that although intercessory prayers for the dead lack soteriological legitimacy within Christian doctrine, the ritual carries profound symbolic and social significance that strengthens community networks. Accordingly, the church is called to develop a contextual and reflective pastoral approach, one that remains rooted in the truth of the Gospel while engaging local cultural realities as a space for witness and transformation.